Analysis of the influence facilities, Quality of Service and Trust on loyalti customer in Star Hotel in Batam City - Muamar Khadafi; Hanny Hanny; Veronica Anugrah (Jurnal Ekonomi LLDIKTI Wilayah 1 (JUKET), 2022)
Every goods and service company is required to make customers feel loyal to the products and services offered. A company is said to be successful and profitable if it finds loyal customers in the long term. Star hotels are hotels with the expectectation that customers have good facilties, service quality and trust. Facility factors, service quality and trust are factors that considered to be able to make loyal customers while staying at five star hotels in the city of Batam. This research is to broaden our insight related to factors that influence customers loyalty in five star hotel in Batam. Based on scientific literature analysis collected from tracing in the last one decade, then variable facility, service quality and trust as variable independence is examined in this research. Research data sources consist of the society population of Batam. As many as 400 samples have been collected and next texted with the assistanced of SPSS 25.0 version. Method of tabulation is using descriptive statistic test, classical assumptive test and hypotheses test. Summary that we have from data analysis process, having the result that explaning facilities influences significantly towards customer loyalty, quality of service influences significantly towards customer loyalty and trust also influences significantly towards customer loyalty. limitation in this research of which there are a lot of other free variety that influence customers loyalty which is not explained in this research, in addition this research may not be able to be forwarded destination and other area and then this questionnaire is less distributed causing it cannot really represent all the opions of asian tourist..